1999
DOI: 10.1038/sj.bjp.0702697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on responsiveness of the mesenteric arterial bed to phenylephrine and KCl in male rats

Abstract: 1 We aimed to determine whether there are any changes in responsiveness of the mesenteric arterial beds to phenylephrine (Phe) and KCl in exercise-trained rats, and whether vascular endothelium and/or vascular smooth muscle play a role in these changes. 2 Adult male rats were subjected to a swimming schedule every day for 28 ± 33 days. Studies were performed in vitro using Krebs perfused mesenteric arterial beds. 3 Maximum perfusion pressure responses to KCl and Phe of the mesenteric arterial beds from exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…To determine this we first analyzed noradrenaline release, observing a huge drop in both basal and EFS-induced noradrenaline release in segments from trained SHRs, in agreement with previous reports describing decreases in plasmatic noradrenaline [38]. Regarding the effect of exercise, increase, decrease and no changes in vasoconstrictor response to alpha-adrenergic agonists have been reported [29][30][31]. In our experimental conditions, we observed that aerobic exercise training increased the vasoconstrictor response to noradrenaline, possibly due to an upregulation process consequent to the decrease in noradrenaline release.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…To determine this we first analyzed noradrenaline release, observing a huge drop in both basal and EFS-induced noradrenaline release in segments from trained SHRs, in agreement with previous reports describing decreases in plasmatic noradrenaline [38]. Regarding the effect of exercise, increase, decrease and no changes in vasoconstrictor response to alpha-adrenergic agonists have been reported [29][30][31]. In our experimental conditions, we observed that aerobic exercise training increased the vasoconstrictor response to noradrenaline, possibly due to an upregulation process consequent to the decrease in noradrenaline release.…”
Section: Discussionsupporting
confidence: 52%
“…KCl vasoconstriction is an indicator of the integrity of intrinsic contractile machinery. Previous reports have shown a lower KCl vasoconstriction in resistance arteries isolated from exercise trained rats [29,30], whereas others have found no differences [31]. This discrepancy could be attributed to differences in the vascular bed analyzed and/or kind of training.…”
Section: Discussionmentioning
confidence: 68%
“…This enhanced relaxation with ACh after exercise training appears to be mediated by both EDHF and NO. Thus, these mediators may counteract the contraction induced by PGF 2· and high K + in isolated vessels, in particular in small arteries, which is similar to the findings reported by Jansakul and Hirunpan [15]. However, modifications of the participation of prostanoids in this enhanced vasodilatory response were not investigated since the experiments were conducted in the continuous presence of indomethacin.…”
Section: Discussionsupporting
confidence: 71%
“…It has been reported that long-term swimming exercise significantly reduces the vasoconstrictive response to phenylephrine in the rat mesenteric artery and thoracic aorta when the endothelium is intact, but not in the endothelium-denuded arteries [26,27] . Chronic exercise also enhances endotheliummediated vasodilatation in the endothelium-intact aorta and mesenteric artery, but this exercise does not affect NA-induced vasoconstriction in the endothelium-denuded arteries isolated from spontaneously hypertensive rats [28] .…”
Section: Wwwnaturecom/aps LI L Et Almentioning
confidence: 99%
“…Moreover, exercise training increases acetylcholine-induced relaxation and eNOS protein levels in the porcine pulmonary artery [29,30] , but not in the pulmonary artery from hypertensive rats [31] . Therefore, we removed the vascular endothelium of the isolated mesenteric, pulmonary, caudal and internal carotid arteries from the rat to directly observe the changes in α 1 -adrenoceptor-and P2X 1 receptor-mediated vascular smooth muscle contractions because several studies suggest that exercise affects not only the vasoconstriction of vascular smooth muscles [32,33] , but also the function of the vascular endothelium [26,27] . NA induces vasoconstriction and vasodilatation via α-adrenoceptors and β-adrenoceptors.…”
Section: Wwwnaturecom/aps LI L Et Almentioning
confidence: 99%